How do students and staff at the University of Cape Town understand equitable access to the curriculum for students with VIs? - Nwanze, Ikechukwu (Department of Health and Rehabilitation Sciences, 2023)
Students with Visual Impairment (VI) s5ll experience barriers to educa5on despite the right to educa5on s5pulated in the United Na5ons Conven5on on the Rights of Persons with Disabili5es (UNCRPD). Challenges such as delays in the conversion of curriculum content to accessible formats, inaccessible online course sites and teaching and learning that is mostly visual. With the University of Cape Town (UCT) going fully online due to COVID-19 pandemic, it became necessary to explore how equitable access to the curriculum is understood. The research topic is: How do staff and students at UCT understand equitable access to the curriculum for students with VIs? Four conceptual framework components were used. The hidden and enacted curriculum was used to explore hidden curriculum aspects and their effect on the enacted curriculum. Universal Design for Learning (UDL) framework was used to explore enablers such as assis5ve technology (AT) and challenges such as inaccessible content. Eight elements of digital literacies were used to explore access to opportuni5es to acquire digital literacies and the UNCRPD to ensure alignment with the right to educa5on. A Q methodology study was conducted which is a hybrid of both quan5ta5ve and qualita5ve methods. It sta5s5cally groups viewpoints that are significantly similar to or dis5nct from each other, quan5ta5vely into factors, then qualita5vely interprets these factors thema5cally to reveal par5cipant views about the research topic. Data was collected from students with VI, lecturers, staff from Disability Services, ICT Services, Library Services, and the Centre for Higher Educa5on Development using Q sor5ng where par5cipants ranked sixty statements into disagree, neutral and agree. Focus group discussions were used to support the interpreta5on of the factors. Findings revealed that: accessible curriculum is also a technical issue which is not priori5sed at UCT, and lecturers struggle with compe5ng demands such lack of 5me, need for promo5on and research. Accessibility design from the start both for curriculum development and support services is not valued. The right to educa5on for students with VI is par5al, varying their experience of the curriculum. Tes5ng of a course site for accessibility and lack of AT nega5vely affects right to educa5on. This study argues that students with VI do not yet enjoy full par5cipa5on in the curriculum due to lack of understanding of the complexity involved. UDL can help academics move from a deficit view to an asset view of students with VI. UCT should change its opera5onal model to accessibility from the start. Then UCT will move closer to equitable access to the curriculum for students with VI.